Influence of suction induced by grass root - Ya’Acob, Nurulfara (2015)
Slope failures problems nowadays are often receive some attention from various parties, especially from the local authority. Although many studies have been conducted to improve slope failures, most studies often ignore the influence of matric suction of vegetation or plants. The conservative solution to prevent the slope failure is by planting grass at the slope. Grass can be classified in many different types and appearance, but for this project, original grass at study area which is known as Cow grass will be used as a study to determine the matric suction due to grass water uptake. The scope of this study will only include grasses and residual soil within the location in the Universiti Teknologi Malaysia (UTM) campus. Any kind of tree would not be involved in this study. Verification of the simulation results for this study will be carried out by conducting measurements at different level of depth of soil to see the pattern of the matric suction. The factor of safety of the soil also has been considered by using parameters data from laboratory testing. The percentage comparison between saturated soil and soil that originally covered by grass is about 64.7% difference. It has shown that vegetation contributes more stability to slope analysis.